Axonal sprouting in layer V pyramidal neurons of chronically injured cerebral cortex - Salin, P (J Neurosci, 1995)
We performed experiments to determine whether axonal sprouting occurs in neurons of chronic neocortical epileptogenic lesions. Partially isolated somatosensory cortical islands with intact pial blood supply were prepared in mature rats. Neocortical slices from these lesions, studied 6–39 d later, generated spontaneous and/or evoked epileptiform field potentials (Prince and Tseng, 1993) during which neurons displayed prolonged polyphasic excitatory and inhibitory synaptic potentials/currents. Single electrophysiologically characterized layer V pyramidal neurons in control and epileptogenic slices were filled with biocytin using sharp and patch-electrode techniques, their axonal arbors reconstructed and compared quantitatively. Neurons in injured cortex had a 56% increase in total axonal length, a 64% increase in the number of axonal collaterals and more than a doubling (115% increase) of the number of axonal swellings. The presumed boutons were smaller and more closely spaced than those of control cells. In some neurons the main descending axon had hypertrophic segments from which branches arose. These highly significant changes were most marked in the perisomatic region of layer V. The axonal sprouting was associated with a decrease in somatic area but no significant change in dendritic arbors. Results suggest that a significant degree of axonal reorganization takes place in the chronically injured cortex where it might be an adaptive mechanism for recovery of function after injury, or might be maladaptive and play an important role in the generation of epileptiform events by increasing the numbers and density of synaptic contacts between neurons.